The Role Of Corporate Governance Mechanism On Voluntary Disclosure - Gunawan, Andrew (Jurnal Akuntansi, 2019)
Basically, the purpose of this research is to examine empirically whether the Corporate Governance is the proportion of independent commissioners, the commissioners who have accounting capabilities, and the proportion of independent auditors can influence disclosure voluntarily. Voluntary disclosure is measured through the complete disclosure of voluntary index (IPS). This index contains 37 items in disclosure in the annual report. The sample is a manufacturing company listed on the Indonesia Stock Exchange, where the data analysis technique that will use the Multiple Regression Analysis using SPSS 23.Ã‚Â